Germany's stake in exchange rate stability - Daniel Gros (Intereconomics, 1996)
The position taken by politicians and important pressure groups in Germany concerning EMU will depend to a large extent on its labour market implications—and thus on the (perceived) impact of exchange rate variability on employment and unemployment. Most economists would assume this impact to be minor. The purpose of this paper is to show that this presumption might be wrong.
Keywords: 330